DEVELOPMENT OF TECHNOLOGY AND ANALYSIS METHODS OF COSMETICS WITH WATER EXTRACTS FROM HERBAL DRUGS RAW MATERIALS - A. A. Chakhirova; N. V. Blagorazumnaya; V. A. Chakhirova; E. Y. Blagorazumnaya (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article presents studies on development of cosmetics with complex extracts from herb of Bidens, flowers of Calendula, and flowers of Matricaria. We cited the analysis methods of the received extract and a drug on its base